The analysis of students’ mathematical connection ability and responsibility in two stay two stray learning with problem cards - Pebriyanti, Maria Metha Dwi; Dwidayati, Nur Karomah; Amidi, Amidi (Unnes Journal of Mathematics Education, 2018)
This research aims to discover mathematics learning on Two Stay Two Stray (TSTS) learning assisted by effective problem cards on students' mathematical connection abilities, describing students' mathematical connection skills based on responsibility for TSTS learning and describing students' responsibilities in TSTS learning. The method used in this research is a mixed method. The population in this research were students of class VII A - VII B on one of junior high schools in Semarang, based on random sampling technique, it was selected that class VII A as the experimental class and class VII B as the control class. The results of the research show that; Students 'mathematical connection ability by using the TSTS model can reach KKM (minimum criteria of mastery learning) and classical completeness, the mathematical connection ability of students by using TSTS learning is better than students' mathematical connection skills by using expository learning. (3) Subjects with high responsibility were able to achieve three indicators of mathematical connection ability well, subjects with moderate responsibility have differences in achieving mathematical connection indicators, subjects with low responsibility were able to achieve one of mathematical connection indicator.